2012
DOI: 10.1103/physrevb.85.054109
|View full text |Cite
|
Sign up to set email alerts
|

Twin boundary spacing-dependent friction in nanotwinned copper

Abstract: The deformation mechanisms of nanotwinned Cu subjected to nanoscratching are investigated by means of molecular dynamics simulations. Scratching simulations on nanotwinned single-crystalline Cu with the twin planes parallel and perpendicular to the scratching direction are performed. Since the detwinning mechanism is completely suppressed in the former case, no apparent correlation between frictional coefficient and the twin spacing is observed. In samples where the twin planes are perpendicular to the scratch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Previous experimental investigations and atomistic simulations have demonstrated that the plastic deformation of polycrystalline NT Cu under friction is governed by several individual deformation mechanisms working in parallel, such as dislocation slip, TB migration, detwinning, deformation twinning and GB-associated mechanism [21][22][23][24]. This work further indicates that the competition between individual deformation mechanisms strongly depends on internal microstructures and loading conditions, i.e.…”
supporting
confidence: 62%
“…Previous experimental investigations and atomistic simulations have demonstrated that the plastic deformation of polycrystalline NT Cu under friction is governed by several individual deformation mechanisms working in parallel, such as dislocation slip, TB migration, detwinning, deformation twinning and GB-associated mechanism [21][22][23][24]. This work further indicates that the competition between individual deformation mechanisms strongly depends on internal microstructures and loading conditions, i.e.…”
supporting
confidence: 62%
“…The transition, with decreasing sample size, from twinning to stacking faults may also be reflected by another approach based on the nucleation process of twins and stacking faults. It has been argued that twinning progresses via partial dislocations and the plane-to-plane propagation of partial dislocation slips. It was then shown that these two steps have opposite size dependence, namely small sample sizes increase the probability of first partial dislocations while decreasing the probability of plane-to-plane propagation of partial dislocation slips. On average, it seems that smaller sample sizes will suppress twinning in this model.…”
supporting
confidence: 71%
“…Investigations of size dependent mechanical twinning under compression have already revealed some grain-size dependence. The grain size effect of twinning has been reported in nanocrystalline Ni and Cu , and has been attributed to the competition between the grain size-dependence of partial dislocations and the layer-by-layer promotion of partial slip near the surface. Hexagonal close-packed Ti–5%Al (atom %) crystal pillars show that the stress required for deformation twinning increases drastically for compression and samples sizes (∼1 μm), below which twins are suppressed and replaced by dislocations .…”
mentioning
confidence: 99%
“…3(b) that variations of SSD thickness for different grinding speeds are at grinding distance 14 nm. Measurement of SSD thickness is based on variations of the potential energy of atoms in different regions with different deformation behaviors [49], and diamond structure atoms excluded for a clearer visualization of the defect structures [50]. Fig.…”
Section: Resultsmentioning
confidence: 99%